Personalization in federated recommendation system using SVD++ with explainability - Patwary, Kabbya Kantam; Jawad, Abid Mohammad; Abir, Md Tahmid Chowdhury; Khushbu, Yuma Tabassum (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.